1991
DOI: 10.1002/app.1991.070420910
|View full text |Cite
|
Sign up to set email alerts
|

Side reactions of phenylisocyanate in N,N‐dimethylacetamide

Abstract: SYNOPSISSide reactions of isocyanate groups in N,N-dimethylacetamide ( DMAC ) were studied. Although 4,4'-diphenylmethane diisocyanate (MDI) in DMAC was stable and no changes occurred at 3"C, the isocyanate content decreased and a gel was finally formed a t 40°C. Using phenyl isocyanate ( P I ) as a model compound of MDI, the identification of PI sidereaction products in DMAC were studied. From these experiments, the following five products were identified; ( 1 ) 1,3-diphenylurea (DPU ), ( 2 ) 1,3-diphenyl-5-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…As assumed by Anzuino et al [25] and Matsui et al [26], the polar character of the solvent might be responsible for the relatively fast secondary reactions occurring in DMSO-d6. It should be noticed than the time required for the acquisition of the 13 C NMR spectrum is incompatible with the rapid evolution of the non neutralized products in DMSO-d6, contrary to some literature indications [28].…”
Section: Methods For Analysis Of the Reaction Products Between Omo Andmentioning
confidence: 88%
See 1 more Smart Citation
“…As assumed by Anzuino et al [25] and Matsui et al [26], the polar character of the solvent might be responsible for the relatively fast secondary reactions occurring in DMSO-d6. It should be noticed than the time required for the acquisition of the 13 C NMR spectrum is incompatible with the rapid evolution of the non neutralized products in DMSO-d6, contrary to some literature indications [28].…”
Section: Methods For Analysis Of the Reaction Products Between Omo Andmentioning
confidence: 88%
“…Authors found that the allophanate/urethane ratio increased with increasing [NCO]/[OH] ratio and temperature. Moreover, an isocyanate compound is not stable in this solvent, since Matsui [26] showed the cyclization of the isocyanate group in DMAc at 40°C. Matsui et al demonstrated that trimerization, which is known to be catalyzed by bases or metals, could take place slowly even without catalyst.…”
Section: Methods For Analysis Of the Reaction Products Between Omo Andmentioning
confidence: 99%
“…Si-doped GaAs normally considered to be of high structural quality is mosaic, although the relative orientations are i 10" (Fewster and Andrew 1993a). As we progress to crystals with dislocation densities -IO4 cm-' then we can see that the cellular structure typical ofsemi-insulating GaAs produces a significant relative orientation of -3 0 (Fewster 1991a, Matsui 1991. The blocks themselves are fairly perfect and approximately 5-10 mm in diameter.…”
Section: Introductionmentioning
confidence: 95%
“…The best approach to avoid thermal pretreatment and enhance NLO response seemed to be the use of reactive solvents with catalytic properties like N , N -dimethylacetamide (DMAC). It is known that DMAC reacts with isocyanates giving N , N -dimethylacetamidines whose further reaction leads to the formation of carbamides and cyclic products like isocyanurates, substituted barbituric acids, and aminouracils. , Some of these reactions occur at a significant rate even at room temperature due to the catalytic effect of DMAC itself. In fact rapid cross-linking of compound DMI 3 was observed when it was dissolved in DMAC after few hours.…”
Section: Resultsmentioning
confidence: 99%